DESIGN AND RELIABILITY ANALYSIS OF ACCOMODATION WORK BARGE MOORING CONFIGURATION AT TENSION LEG PLATFORM IN MAKASSAR STRAIT - Juan Tanujaya - NIM 15514022 , Antonio
Tension Leg Platform (TLP) is one of the floating offshore platforms that suit to operate in deepwater oil and gas field. Once in a lifetime of an oil field facilities, a well intervention usually needed to make an improvement of the well which needs extra facilities for accomodation. An Accomodation Work Barge (AWB) is working at TLP in Makassar Strait for a well intervention project. The system installed with 4 mooring lines D1 to D4 which tied up to the north of the vessel, whilst 4 hawser lines connect TLP to the south lines of the vessel and is fitted with 2 lines TH1 and TH2 on the south side. However the TH lines are having a failure issue due to unknown reason. Therefore, a redesign and reanalysis is performed to evaluate the required mooring pattern, properties to support AWB operation at TLP using API RP2SK standard. The criteria control the line tension limit, TLP offset, and mÃƒÂnimum clearance between facilities. Reliability assessment will provide reliability index (𝛽) of design recomendation wether TH mooring lines are required or could be eliminated. Mooring analysis is performed using ORCAFLEX for intact and damaged condition, while a Monte Carlo simulation is performed to get the system failure probability with mÃƒÂnimum breaking strength ratio (%MBS) acted as the parameter. From the mooring analysis results, it is found that TH lines can be eliminated as it doesnÃ‚Â’t give a significant results to the whole system check. The worst case which will be analyzed further on the reliability analysis is the line tension from D4 in the 100YRP conditions from North. The analysis deliver a reliability index 𝛽 = 14.676 which is greater than the reccomendation for an offshore structure (𝛽 = 3.71). The results show that the mooring system is very secure with a very high reliability index.